Prevention of Saprolegniasis in rainbow trout (Oncorhynchus mykiss) eggs using oregano (Origanum onites) and laurel (Laurus nobilis) essential oils - Özdemir, Rahmi Can; Taştan, Yiğit; Güney, Kerim (Wiley, 2021)
AbstractThe present study investigated the antifungal effects of essential oils of oregano (Origanum onites) and laurel (Laurus nobilis) on Saprolegniasis, a disease that occurs in rainbow trout eggs during the incubation period. Oregano and laurel were ground after drying, and essential oils were obtained by water distillation method using a Clevenger apparatus. The essential oils were added to potato dextrose agar (PDA) at the rates of 1–1000 ppm, and the minimum inhibitory concentration (MIC) was determined as 250 ppm whereas the minimum lethal concentration (MLC) was determined to be 500 ppm for both plants. In the in vivo trials, fertilized eggs were treated with predetermined doses either by bathing during water hardening and incubation period or only during incubation period, and death rates were monitored during embryological development. The best larvae hatching rate was determined in 500 ppm oregano and 500 ppm laurel groups treated during water hardening plus daily as 82.11% and 79.87%, respectively. According to the results, it was determined that oregano and laurel essential oils exhibited better results in all doses compared with the negative control group, and 500 ppm dose had a better effect than the positive control group treated with formalin.
Keywords: Fish Diseases; Oncorhynchus mykiss; Origanum; Oils, Volatile; Animals; Laurus; 6. Clean water; 3. Good health